O manejo odontológico da ulceração aftosa recorrente em crianças: uma revisão integrativa - GUILHERME DE CAMPOS CAPILÉ (2023)
Recurrent aphthous ulceration (UAR) is one of the most common diseases of the oral mucosa, with a higher prevalence and morbidity in children. The objective of this study was to list the forms of treatment available in the literature for UHR in childhood. An integrative review was carried out in the PubMed, Virtual Health Library, Scopus and Scielo databases, selecting complete articles in English, Spanish, French and Portuguese published in the last 20 years, with the keywords “aphthous stomatitis” and “treatment”. with “child”, “children” or “pediatric”. The search identified 1506 articles, 8 of which were selected after applying the inclusion and exclusion criteria. There was a variety of demographics, therapeutic options and sample size. Although the focus of the review was on the pediatric population (up to 12 years old), three studies included adolescents (12 to 18 years old) in their samples. Among the therapeutic options, supplementation with vitamins and minerals and topical application of hyaluronic acid and dexamethasone stood out. Management was also carried out with photobiomodulation, herbal medicine, probiotics, and topical anesthetic. In general, the treatments resulted in a reduction in the lesion, improvement in pain and good tolerance by patients and guardians, highlighting the absence of side effects in this population and the lack of standardization of the therapies used. It is essential that the dentist is aware of the therapeutic options for UHR to quickly implement the treatment, as it can generate important comorbidity for the patient.